Redesigning the Visual Identity of Metro Culinary Tourism Destinations in Metro City - Azizah, Putri Sabrina Nur; Moussadecq, Ade; Aditya Putra, Ambar (IMAGIONARY, 2023)
The phenomenon of copy pasting the Jamur Sawah culinary tourism logo is more directed to the element of plagiarism. The weak visual identity of this Jamur Sawah culinary tourism destination, in the future will complicate the branding process. The purpose of this design is to carry out a redesign (re-design) process as an effort to strengthen Jamur Sawah's position in market competition and eliminate elements of plagiarism contained in the logo. Mushroom Rice. The data explored in this study include sketching, designing alternative designs for the Jamur Sawah logo, and logo application (billboards, signboards, flyers and xbanners, corporate signatures, stationary sets, and merchandise). Data from interviews, observations, and literature were analyzed using qualitative methods. The problem analysis method in redesigning Jamur Sawah's visual identity uses the mindmapping method followed by the brainstorming method. Jamur Sawah culinary tourism logo is an interpretation of persuasively inviting to visit Mushrooms (Cheap Snacks) Sawah which sells delicious, hygienic, and affordable food. The result of this research is a visual identity design as a logo using the main media of the Kentucky Fried Chicken (KFC) logo which includes color and mascot. The logo from the redesign of the visual identity of the mushroom field culinary tourism destination was then applied through publications, corporate signatures, stationary sets, and merchandise.